The Art Gallery : Workbook. (Prahran : The Art Gallery)
Barberis, Irene ; Bilu, Asher ; Brooks, Ailsa ; Davis, John ; Flint, Tony ; Gregory, Bill ; Hare, Graeme ; Hughes, Maurie ; Juraszek, Paul ; Kunishima, Seiji ; Meertens, Victor ; O'Brien, Brad ; Quinn, Loretta ; Romeo, Giuseppe ; shaw, Jeffrey ; Valamanesh, Hossein
The Art Gallery, Prahran, Melbourne (Victoria) [1988-1989]
boek